Qishen Yiqi Dripping Pill Protects Against Diabetic Nephropathy by Inhibiting the Wnt/β-Catenin and Transforming Growth Factor-β/Smad Signaling Pathways in Rats - Zhang, Qian; Xiao, Xinhua; Zheng, Jia; Li, Ming; Yu, Miao; Ping, Fan; Wang, Tong; Wang, Xiaojing (Frontiers in Physiology, 2021)
Diabetic nephropathy (DN) is a severe microvascular complication of diabetes. Qishen Yiqi Dripping Pill (QYDP) has been reported to be a renal protective drug. However, the mechanisms remain unclear. This study was performed to investigate the mechanisms. In this study, Sprague-Dawley (SD) rats were fed a high-fat diet and injected with streptozotocin (STZ) to generate a diabetes model. Diabetic rats were administered 150 mg/kg/d or 300 mg/kg/d QYDP. After 8 weeks of treatment, serum creatinine, serum blood urea nitrogen (BUN) and 24-h urinary albumin were measured. Kidney histological staining and immunostaining were analyzed. Then, the renal tissue was analyzed with a genome expression array. The results showed that QYDP treatment reduced serum creatinine, BUN and 24-h urinary albumin and improved kidney histology and fibrosis. The gene array revealed that the expression of 189 genes was increased and that of 127 genes was decreased in the high dosage QYDP group compared to the diabetic group. Pathway and gene ontology analyses showed that the differentially expressed genes were involved in the Wnt/-catenin and TGF-/smad2 signaling pathways. QYDP reduced the renal Wnt1, Ctnnb1, Tgfb1 and Smad2 gene expression and -catenin, TGF-, Smad2, collagen Ⅰ, α-SMA, and fibronectin protein expression in diabetic rats. Our results provide the first evidence that QYDP performs its renal-protective function by inhibiting the Wnt/-catenin and TGF-/smad2 signaling pathways in diabetic rats.